2018
DOI: 10.3390/beverages4040098
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Drivers of Muscadine Wine Purchase Decisions

Abstract: Muscadine wine, fresh muscadine grapes, and other derivatives have enjoyed a heritage niche for decades in the Southeast. Muscadine growers in North Carolina in the United States (US) have asked whether the purchase of muscadine wine is linked to consumption of the fruit itself or even familiarity with other muscadine-based products in terms of spillover effects. The authors explored the interdependency between the market for fresh muscadine grapes and muscadine wine purchase. Consumer panel data were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…An additional advantage here is greater satisfaction for producers, becauseas indicated by Pijet-Migoń and Królikowska (2020) -their production maintains and develops the cultural heritage of a given area. The second issue related to the increase in demand for wines can be stimulated -as noted by Canziani et al (2018) -through educational activities and increasing consumer awareness. So it is one of the most important issues in the production of wines.…”
Section: Discussionmentioning
confidence: 99%
“…An additional advantage here is greater satisfaction for producers, becauseas indicated by Pijet-Migoń and Królikowska (2020) -their production maintains and develops the cultural heritage of a given area. The second issue related to the increase in demand for wines can be stimulated -as noted by Canziani et al (2018) -through educational activities and increasing consumer awareness. So it is one of the most important issues in the production of wines.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that familiarity with muscadine products (wine, jams, jellies, health products, etc.) positively influences the purchasing of muscadine wine in the southern U.S. [61]. A key aspect in the expansion of the muscadine market will therefore be the development of products that appeal to consumers outside of the region and to those with no prior experience with muscadines.…”
Section: A Future Prospectus For Increased Production Market Awarenementioning
confidence: 99%
“…A key aspect in the expansion of the muscadine market will therefore be the development of products that appeal to consumers outside of the region and to those with no prior experience with muscadines. While belief about muscadine's health benefits was only slightly influential in consumer decision to purchase muscadine wine [61], muscadine has tremendous nutritional benefits. Muscadine may be considered a super food due its high concentration of phenolic compounds [62] and compounds shown to limit cancer growth [62].…”
Section: A Future Prospectus For Increased Production Market Awarenementioning
confidence: 99%